INSECURITY AND RIGHT TO HEALTH OF NIGERIANS: CHALLENGES AND SOLUTIONS - Egbue, N.G.; Nwankwo, Ignatius Uuche (European Scientific Journal, ESJ, 2014)
The worsening state of insecurity of lives and property in Nigeria is a major source of concern to both Nigerians and the international community. The effects of insecurity on socio-economic activities, psyche and overall functioning of Nigerians are tremendous. This review paper critically examines how insecurity affects right to health of Nigerians. Right to health is defined in terms of ease of access to acceptable and affordable health service, at fully equipped, well staffed, and functional public health institutions sited close to the doorsteps of individuals. Anchored on functionalism and structural strain theories, the paper argues that insecurity negatively undermines pursuit of right to health of Nigerians. It recommended the use of dialogue to check rising threats to lives and property across Nigeria. Strengthening of economic empowerment and social re-orientation programmes by the government was also canvassed to calm aggrieved unemployed youths. The paper concluded that it is only in an atmosphere of peace and security that right to health of Nigerians will be fully realized.